Complete heart block as a complicating feature of a mediastinal lymphoma. (30th April 2012) - Jorge, Vanda Cristina; Bernardino, Vera; Araújo, Ana Carolina; Gomes, Sara; Noronha, Carla; Riso, Nuno; Vaz Riscado, Manuel
Abstract : Malignant lymphomas represent about 9% of cardiac neoplasms. Despite its life-threatening nature, the cardiac manifestations are often subclinical. In about 20% of deaths from lymphoma, cardiac involvement is found only in autopsy. The authors present the case of a 77-year-old female admitted due to intense back pain, vomiting, generalised pruritus, fatigue and weight loss. She had a personal history of hypertension and breast cancer was noted 10 years before admission. The thoracoabdominopelvic CT showed a mass in the left atrium with extension to the right atrium and inferior vena cava, and a paravertebral mass at D10-D11 with invasion of the spinal canal and hepatic hilum. The transthoracic paravertebral mass biopsy was compatible with a diffuse large B cell lymphoma. The patient developed a complete atrioventricular block, with haemodynamic instability, requiring urgent chemoreduction of the paracardiac mass and implantation of an epicardial pacemaker.